How Can Capital Investment Improve the Development Level of University Informatization? A Moderated Chain Mediation Model - Zhu, Zhen; AlGerafi, Mohammed A.M.; Wan, ShuFen; Lu, CiXian (Transformations In Business & Economics, 2025)
Under the background of the digital transformation of education, increasing capital investment to promote the construction of university informatization is an important measure to boost the high-quality development of higher education. However, there is no systematic explanation and demonstration of the internal mechanism, logic, and conditions through which funds affect the development of university informatization. Because of this, this paper attempts to build a moderated chain mediation model based on literature review. Using official data from 95 universities in Zhejiang province to evaluate the informatization development level, descriptive statistics, correlation analysis, regression analysis, and mediation and moderation effects were conducted using SPSS 26 and Process V3.5 plugins to explore the impact of capital investment on the informatization development level of universities. The results show that capital investment in college informatization construction can significantly and positively affect the level of informatization development. Information leadership and human resource investment in colleges and universities play an intermediary role in the relationship between capital in-vestment and information development level. The mechanism of university informatization construction positively regulates the relationship between human resource investment and informatization development level. Additionally, the mechanism of university informatization construction positively regulates the indirect effect of capital investment on the level of informatization development. The research results reveal the internal mechanism and function path of "how the capital investment affects the development level of university informatization” and pro-vide beneficial enlightenment for universities to make full use of informatization funds to conduct construction practices.
Keywords: higher education; digital transformation; capitalization method; action mechanism; sustainable informationization